No more Sabado nights [videorecording] - Philippine Center for Investigative Journalism; Magsanoc, Kara. (Quezon City PCIJ, 1996)
No more Sabado nights tells the story of how the women of Tawid Sapa organized themselves against wife beating, set up a refuge for battered women, and even got the government to install electric lines and dig deep wells in their community.
Keywords: Battered wives -- Philippines; Women -- Philippines; Women -- Tawid Sapa, Novaliches